Religious Moderation within Indonesian Diaspora in Australia’s Secular Society - Ma'mun, Sukron; Nuroniyah, Wardah; Salim, M Arskal; Maula, Bani Sarif; Shodikin, Akhmad (AL-TAHRIR, 2025)
This study investigates the concept and practice of religious moderation within the Indonesian diaspora community in Australia, with a focus on how members navigate religious identity in a Western, secular society. Grounded in the four pillars of religious moderation established by Indonesia’s Ministry of Religious Affairs—national commitment, tolerance, anti-violence, and accommodation of local cultural values—the research employs a hybrid methodology combining online and in-person interviews, as well as direct observation, drawing on the author's field experience in Sydney. The findings highlight three core dimensions. First, the practice of religious moderation is significantly shaped by diaspora organisations such as PCI Nahdlatul Ulama Australia-New Zealand, PCI Muhammadiyah Australia, the Iqro Foundation, and the Indonesian Diaspora Network (IDN), which promote inclusive religious practices and enhance community cohesion. Second, Australian public institutions play a vital role in fostering values such as religious freedom and pluralism, providing a supportive environment for the diaspora to sustain their cultural and religious identities. Third, the Indonesian diaspora demonstrates effective acculturation by preserving religious traditions while adapting to Australia’s multicultural landscape, despite ongoing challenges related to identity negotiation in a pluralistic context. The study concludes that the Indonesian diaspora in Sydney exemplifies a resilient model of religious moderation through inclusive engagement, institutional collaboration, and cultural adaptation, offering valuable insights for broader discussions on religion, migration, and pluralism in global settings.